A review on rear under-ride protection devices for trucks. Issue 1 (2nd January 2017) - Albahash, Zeid Fadel; Ansari, M.N.M.
ABSTRACT: A rear under-ride protection device is a metal structure that is found on the rear side of the trucks usually made of steel. At present some of the countries claimed to have developed 'under-ride protection device' to address the problems related to automobile crashes especially car colliding with a truck from its rear side. However, the crashes lead to fatal ends due to the poor performance of the under-ride protection devices. This review is aimed to discuss the crashworthiness of vehicles under collisions, specific energy absorption during accidental impacts, energy absorbing systems, various types of materials used for energy absorption, under-ride protection devices and various types of under-ride protection devices that exist in the current market.